2004
DOI: 10.1117/12.529442
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond laser silicon micromachining

Abstract: We present theoretical calculations and experimental measurements of silicon micromachining rates, efficiency of laser pulse utilization, and morphology changes under UV nanosecond pulses with intensities ranging from 0.5 GW/cm 2 to 150 GW/cm 2 . Three distinct irradiance regimes are identified based on laser intensity. At low intensity, proper gas dynamics and ablation vapor plume kinetics are taken into account in our theoretical modeling. At medium high intensity, we incorporate the proper plasma dynamics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…In zone 3, ablation rate dramatically increases with the increase of laser fluence and may get saturated, while the processing quality degrades significantly and the dimensions of the ablation generated defects is less controllable. Ren et al 152 found that for UV nanosecond laser pulses with intensities ranging from 0.5-150 GW/cm 2 , at low ablation intensity, silicon removal is characterized by surface evaporation and the ablation morphology is clean. At medium ablation intensity, the increment of ablation rate with laser intensity slows down and saturates due to a strong plasma shielding effect and the quality of laser ablation is degraded.…”
Section: Laser Dicingmentioning
confidence: 99%
“…In zone 3, ablation rate dramatically increases with the increase of laser fluence and may get saturated, while the processing quality degrades significantly and the dimensions of the ablation generated defects is less controllable. Ren et al 152 found that for UV nanosecond laser pulses with intensities ranging from 0.5-150 GW/cm 2 , at low ablation intensity, silicon removal is characterized by surface evaporation and the ablation morphology is clean. At medium ablation intensity, the increment of ablation rate with laser intensity slows down and saturates due to a strong plasma shielding effect and the quality of laser ablation is degraded.…”
Section: Laser Dicingmentioning
confidence: 99%
“…Many types of surface structures develop spontaneously on silicon surfaces after repeated nanosecond laser irradiation pulses. A different morphology is observed at the bottom of the craters formed by a few high-power pulses (Craciun et al, 2002;Ren et al, 2004). Sharp conical microstructures separated by 20-30 mm are created on silicon surfaces with nanosecond laser irradiation generated in multi-pulsed regime (Crouch et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Por lo tanto se decidió fijar la frecuencia de repetición, que por motivos de estabilidad de los equipos fueron 20 kHz, para el caso de radiación UV y VIS, y de 4 kHz para el caso de radiación IR. A modo de recapitulación se representan Los datos obtenidos de fluencias umbrales son un poco menores que los obtenidos en c-Si puro por otros autores [Ren04,kamakis06,Tao09,Colina08A]. Poder comparar resultados es difícil dado el carácter exclusivo de nuestra muestra y el hecho de que la elección del área que define la fluencia puede no ser única.…”
Section: Evaluación De Los Procesos Láserunclassified